A Fight Againts The Social Injustice In Charles Dickens' The Tale Of Two Cities; A Marxist Approach - Hartono, Daisy Ronniasih (2012)
This research is aimed at analyzing the structural elements of A Tale of Two Cites and describing a fight againts the social injustice in the story based on Marxist approach. The study focuses on a fight againts social injustice. The major problem of this study is how a fight againts the social injustice is reflected in Charles Dickens' A Tale of Two Cities based on Marxist Approach. This research paper is descriptive qualitative research. The object of the study is A Tale of Two Cities novel written by Charles Dickens. The primary data source is A Tale of Two Cities itself and the secondary data sources are several references, literary criticism, and articles from internet. The method of collecting data is library research. The technique of data analysis is descriptive analysis. The result of the study reveals the way of fight againts the social injustice in Charles Dickens' that was inspired by the French Revolution which ranged from 1789 to 1793, involved an overthrow of the aristocratic ruling order by the lower classes and was followed by a period of terror. Starting from the polarization of classes, the cruel and unjust condition, and Revolutionary movement has led the writer to conclude that Dickens' A Tale Of Two Cities clearly reflected the Marxism theory